Injury Severity and Disability Outcomes Following Motorized Two-Wheeler Crashes in Lahore, Pakistan: A Follow-Up Study - Amjad Iqbal Burq, Muhammad Saleem Rana, Ejaz Ahmed Qureshi, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Road traffic crashes are a leading global cause of mortality and disability, with motorized two-wheeler riders among the most vulnerable road users. In Pakistan, rising motorcycle use has been accompanied by increased crash-related injuries, particularly head and neck trauma, resulting in long-term social and economic consequences. Objective: To determine the severity of injuries and disability outcomes among victims of motorized two-wheeler crashes through a follow-up study. Methods: This prospective cohort study was conducted at the trauma centers of Mayo Hospital, Jinnah Hospital, and Lahore General Hospital, Lahore, between April and June 2022. Using non-probability convenience sampling, 295 injured or deceased two-wheeler riders were included. Riders of any age or gender involved in road traffic crashes were eligible, while non-road trauma cases were excluded. Patients were followed for one month to assess post-injury outcomes, including incapacity, disability, disfigurement, and recovery. Results: Of the participants, 49.2% sustained head and neck injuries, 46.8% had multiple body injuries, and 4.1% had limb injuries only. At one-month follow-up, 51.0% were incapacitated, 17.0% developed disabilities affecting routine work, 14.6% had disfigurement, and 7.1% reported scarring. Complete recovery was achieved in only 5.4% of cases. Middle-aged adults constituted the most affected group. Conclusion: Motorized two-wheeler crashes are associated with high rates of head and neck injuries, long-term incapacity, and disability. Middle-aged adults are disproportionately affected, reflecting major socioeconomic implications. Preventive measures, especially strict helmet enforcement and road safety interventions, are urgently needed. Keywords: Motorized two-wheeler crashes; Injury severity; Disability outcomes; Head and neck injuries; Road traffic accidents.